Effect of budding height and forcing method on citrus nursery-tree production - Vasconcellos, Luiz A.B.C. de; Simão, Salim; Vasconcellos, Francisco T.C. de (Pesquisa Agropecuaria Brasileira, 2014)
'Pera' sweet orange (Citrus sinensis (L.) Osbeck) budwood was budded on field-grown Rangpur lime (Citrus limonia Osbeck) seedlings. Budding heights compared were 5 cm and 20 cm, and forcing methods were topping and lopping. There were no effects of height or forcing method on bud take. Length of the main axis, however, was affected. Lopping resulted in longer axis when budding height was 20 cm, but there was no difference for a 5 cm height. A budding height of 5cm induced longer axis when the forcing method utilized was topping, but no difference resulted when lopping was used.